LABORATORY VALIDATION AND FIELD VERIFICATION OF SILICA GEL SAMPLING TUBE FOR MEASURING ETHYLENE OXIDE IN AIR - Chong, Kian Wei; Ibrahim, Md. Sani; Goh, Teik Beng (Malaysian Journal of Science, 2012)
A sampling and analytical method for the measurement of ethylene oxide (EtO) level in air was developed. The procedure was based on the entrapment of ethylene oxide in an activated silica gel adsorbent inside a sampling tube. The ethylene oxide was desorbed by distilled water and the eluent was analyzed by gas chromatography with flame ionization detector. Parameters such as breakthrough volume, method detection limit, desorption efficiency and storage tests for 14 days in ambient temperature and refrigerator were determined. Field samplings were performed at two factories in Kulim and Pulau Pinang respectively, which use ethylene oxide gas as sterilization substance. The desorption efficiency of ethylene oxide from silica gel tube was determined to be 87.8% over concentration range of 0.2 – 4.0 ppm in 3 liters of air sample. The method detection limit was determined to be 1.0 ppm whereas the precision of procedure was 10.7%. All the parameters were shown to be meeting OSHA requirements. ABSTRAK Satu kaedah persampelan dan analisis untuk mengukur tahap etilena oksida dalam udara telah dibangunkan. Prosedur ini berasaskan pemerangkapan etilena oksida dalam penjerap gel silika yang telah diaktifkan dalam suatu tiub persampelan. Etilena oksida telah didejerap dengan menggunakan air suling dan eluen tersebut dianalisis dengan gas kromatografi yang dielengkapi dengan pengesan pengionan nyala. Parameter seperti keberkesanan pendejerapan etilena oksida daripada tiub silika, isipadu penembusan, had pengesanan kaedah, keberkesanan pendejerapan dan ujian penyimpanan selama 14 hari pada suhu ambien (270C) dan suhu peti sejuk (40C) telah ditentukan. Persampelan lapangan telah dilakukan di dua buah kilang masing-masing di kulim dan Penang yang menggunakan etilena oksida sebagai bahan pensterilan. Keberkesanan pendejerapan etilena dioksida daripada tiub gel silica telah ditentukan sebagai 87.8 % pada julat kepekatan 0.2-4.0 ppm untuk tiga liter sampel udara. Had pengesanan kaedah telah ditentukan sebagai 1.0 ppm manakala kejituan prosedur adalah 10.7 %. Semua parameter yang dikaji menunjukkannya memenuhi syarat OSHA. (Keywords: Indoor air pollution monitoring, ethylene oxide (EtO), desorption efficiency, breakthrough volume)